Anaerobic bacteria in wastewater treatment plant - Cyprowski, Marcin (Int Arch Occup Environ Health, 2018)
PURPOSE: The objective of this study was to assess exposure to anaerobic bacteria released into air from sewage and sludge at workplaces from a wastewater treatment plant (WWTP). METHODS: Samples of both sewage and sludge were collected at six sampling points and bioaerosol samples were additionally collected (with the use of a 6-stage Andersen impactor) at ten workplaces covering different stages of the technological process. Qualitative identification of all isolated strains was performed using the biochemical API 20A test. Additionally, the determination of Clostridium pathogens was carried out using 16S rRNA gene sequence analysis. RESULTS: The average concentration of anaerobic bacteria in the sewage samples was 5.49 × 10(4) CFU/mL (GSD = 85.4) and in sludge—1.42 × 10(6) CFU/g (GSD = 5.1). In turn, the average airborne bacterial concentration was at the level of 50 CFU/m(3) (GSD = 5.83) and the highest bacterial contamination (4.06 × 10(3) CFU/m(3)) was found in winter at the bar screens. In total, 16 bacterial species were determined, from which the predominant strains belonged to Actinomyces, Bifidobacterium, Clostridium, Propionibacterium and Peptostreptococcus genera. The analysis revealed that mechanical treatment processes were responsible for a substantial emission of anaerobic bacteria into the air. In both the sewage and air samples, Clostridium perfringens pathogen was identified. CONCLUSIONS: Anaerobic bacteria were widely present both in the sewage and in the air at workplaces from the WWTP, especially when the technological process was performed in closed spaces. Anaerobic bacteria formed small aggregates with both wastewater droplets and dust particles of sewage sludge origin and as such may be responsible for adverse health outcomes in exposed workers.